Media Gambar Berseri untuk Meningkatkan Kemampuan Menulis Teks Deskripsi Siswa - Sutiyani Sutiyani; Rahmat Rahmat; Andi Puspitasari (DIDAKTIS : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
This research discusses the process and improvement of descriptive text writing skills among Grade XI Accounting students at SMKN 2 Buton Tengah through the use of picture series media. The objective of this study is to improve students’ writing performance and their engagement during the learning process. This study employed Classroom Action Research (CAR) carried out in two cycles. The data analysis techniques used were descriptive qualitative and quantitative methods. The results showed that student activeness in the first cycle reached 84% in the first meeting and increased to 85% in the second. In the second cycle, activeness further increased to 95%. The students’ average writing score in the pre-cycle was 55.54 with a mastery rate of only 14%. In the first cycle, the average score improved to 72.47 with 62% mastery, and in the second cycle, it rose to 85.34 with 90% mastery. Based on these results, it is concluded that picture series media are effective in improving both students’ descriptive writing skills and their classroom engagement.